The dialectic of practice and the logical structure of the tool : philosophy, archaeology and the anthropology of technology - Kozatsas, Jannis (Praehistorica Mediterranea, 2020)
The Dialectic of Practice and the Logical Structure of the Tool undertakes a critical review of recent trends in the archaeological and anthropological theory of technology from processual neo-positivism and postprocessual relativism to the contemporary French and American anthropology, and the symmetrical theory of material culture. On the basis of a critique of their logical premises and epistemological consequences, it draws on the tradition of Hegelian dialectics in order to propose an alternative understanding of technology as a material social practice within which the subject and the object -the socio-cultural and the natural- are produced concurrently as inter-constituted elements, and they are unified through their mutual negative relation to each other.